2015
DOI: 10.1371/journal.pone.0119908
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency in Sickle Cell Disease: A Systematic Review

Abstract: Vitamin D deficiency has emerged as a public health focus in recent years and patients with sickle cell disease (SCD) reportedly have a high prevalence of the condition. Our objectives were to summarize definitions of vitamin D deficiency and insufficiency used in the literature, and to determine the prevalence and magnitude of each in patients with SCD through a systematic review conducted according to PRISMA guidelines. From a PubMed search, 34 potential articles were identified and 15 met eligibility criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 64 publications
5
55
0
4
Order By: Relevance
“…Another important finding was that almost half of SCA patients have vitamin D deficiency. These results are in line with those of previous studies on prevalence of vitamin D deficiency among SCA patients which was mentioned in the literature review [19]. Anyhow, previous reports on vitamin D levels in normal population of KSA, indicated that the majority of Saudis have low vitamin D levels mostly due to low dietary intake and sunlight avoidance [26].…”
Section: Discussion:-supporting
confidence: 91%
See 2 more Smart Citations
“…Another important finding was that almost half of SCA patients have vitamin D deficiency. These results are in line with those of previous studies on prevalence of vitamin D deficiency among SCA patients which was mentioned in the literature review [19]. Anyhow, previous reports on vitamin D levels in normal population of KSA, indicated that the majority of Saudis have low vitamin D levels mostly due to low dietary intake and sunlight avoidance [26].…”
Section: Discussion:-supporting
confidence: 91%
“…Vitamin D and calcium levels are critical factors for maintaining an optimum healthy bone structure [7]. Due to multiple factors, patients with SCD reported to have higher prevalence of Vitamin D deficiency than normal population, defining deficiency as vitamin D below 20 ng/ml, it ranged from 56.4% to 96.4% [19]. Moreover, they found that patients with bone involvement like AVN and vertebral compression fractures had associated vitamin D deficiency [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another report by showed patients with SCA had low calcium and vitamin D 3 (below the normal range) in 14% and 12%, respectively, with PTH significantly higher (31% with values above normal range) 33. A possible cause of hypocalcemia and vitamin D 3 deficiency is impaired intestinal absorption of calcium and vitamin D, leading to the disturbed calcium metabolism seen in SCA 33,34…”
Section: Discussionmentioning
confidence: 99%
“…Furtheremore, the severity of NE increases as the level of 25(OH) D decreases [133]. Using the same definition in a systematic analysis, the prevalence of vitamin D deficiency was reported to range from 56.4to 96.4% in children with SCA [134].…”
Section: Vitamin Dmentioning
confidence: 99%